2014
DOI: 10.3892/ol.2014.1878
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 promoter hypermethylation in sporadic epithelial ovarian carcinoma: Association with low expression of BRCA1, improved survival and co-expression of DNA methyltransferases

Abstract: The breast cancer susceptibility gene 1 (BRCA1) inactivation in sporadic epithelial ovarian carcinoma (EOC) is common and low BRCA1 expression is associated with promoter hypermethylation. The clinical validation of BRCA1 methylation as a prognostic marker in EOC remains unresolved. The aim of the present study was to determine the aberrant promoter methylation of BRCA1 in benign and malignant ovarian tumor tissues, to establish the association with the clinicopathological significance and the prognostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
2
24
0
2
Order By: Relevance
“…Chiang et al demonstrated survival disavantage in patients whose neoplasm were methylated at BRCA1 (Chiang et al, 2006). However, reported significant association between BRCA1 gene methylation and improved survival rate in patients with advanced stage (stage III-IV) (Bai et al, 2014). The inconsistency of these results may be due to the varying population and different environtment condition that were involved in the studies.…”
Section: Discussionmentioning
confidence: 46%
“…Chiang et al demonstrated survival disavantage in patients whose neoplasm were methylated at BRCA1 (Chiang et al, 2006). However, reported significant association between BRCA1 gene methylation and improved survival rate in patients with advanced stage (stage III-IV) (Bai et al, 2014). The inconsistency of these results may be due to the varying population and different environtment condition that were involved in the studies.…”
Section: Discussionmentioning
confidence: 46%
“…BRCA1 , which is a typical tumor suppressor gene, contributes to the regulation of transcriptional activation, DNA repair, apoptosis, cell-cycle checkpoint control and chromosomal remodeling (28). A previous meta-analysis has provided evidence that BRCA1 methylation is associated with the poor survival of patients with BC (34).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of BRCA1 and GSTP1 was evaluated using the semi-quantitative scoring criteria according to the staining intensity (0, negative; 1, weak; 2, moderate; and 3, strong) and the proportion of positive cells (0, positive in ≤5%; 1, positive in >5 and ≤25%; 2, positive in >25 and ≤50%; 3, positive in >50 and ≤80%; and 4, positive in >80% tumor cells). The two scores were multiplied together for each case and gene expression was subsequently graded as: 0, negative score; 1–4, weak expression score; 5–8, moderate expression score; and 9–12, strong expression score (28). …”
Section: Methodsmentioning
confidence: 99%
“…The low expressions of BRCA1 and BRCA2 genes have also been reported in solid tumours, such as epithelial ovarian carcinoma, prostate cancer and breast cancer 31 32. Using MLR analysis, we detected that decreased expression of BRCA2 was associated with an increased chance of developing hMDS with an OR of 12.…”
Section: Discussionmentioning
confidence: 54%